WORKING CAPITAL MANAGEMENT OF PT PERKEBUNAN NUSANTARA VIII - Camelia Rizki Agrina (Gapenas Publisher, 2023)
PT Perkebunan Nusantara is a state-owned company in the agriculture sector. The main commodities that managed by PTPN VIII are Tea, Palm Oil, and Rubber. PTPN VIII current condition is showing the decreasing in current ratio. This indicates that The Company does not manage their working capital optimally. The aim of this research is to give an optimal working capital management and also working capital financing strategy for the Company. Managing current assets (inventory and account receivable) and current liabilities (account payable) are present in this research. Inventory managed by finding the optimal level of inventory and suggest the selling policies for The Company. Account receivable management that used in this research is relaxing the credit standard and account payable management to get the optimal credit terms from the supplier without damaging credit rating. The management of current asset and current liabilities positively impact to Cash Conversion Cycle (CCC). The result of this research shows that conservative financing strategy will result in the less expensive cost compared with aggressive financing strategy.